Optimization and storage study of value-added vinegar from guava (Psidium guajava) cultivars - Anju Kumari; Rakesh Kumar; Siddqui, Saleem (Current Horticulture, 2025)
Two strains of Acetobacter aceti (MTCC 2945 and MTCC 3245) were compared on the basis of variation in inoculation size (5, 10 and 15%) and incubation time (22, 48 and 72 hours) to produce vinegar from guava (Psidium guajava L.) cv. Hisar Surkha and Hisar Safeda at CCS Haryana Agricultural University, Hisar, Haryana. Vinegar was further value-added by ginger (Zingiber officinale L.), garlic (Allium sativum L.), and beetroot (Beta vulgaris subsp. Vulgaris). Value-added garlic vinegar had maximum overall acceptability, hence was further stored for 45 days and examined for its physicochemical analysis. During storage value-added garlic vinegar had low acetic acid, ascorbic acid, antioxidant activity and alcohol content. The value-added garlic vinegar can be served as a functional food, and can be used for preservation of food products like pickles, gherkins, sauerkraut etc.